The Hidden Curriculum and its Role in Students’ Acquisition of Cultural Values and Behavioral Patterns - Alkriameen, Hani Ahmad; Qarareh, Ahmed Odeh (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to investigate the role of the hidden curriculum in students ’acquisition of values, behaver’s patterns, the study sample consisted of (50) students. They were asked about the what the values and behaver’s patterns that they acquired from the school. After analyzed students answers, the results of the study indicated that there are many values were acquired by students such as: - the value of honesty, respect for time, the way of speaking, respect for others, elegance, influence in writing and writing And good words, and despite the students ’acquisition of these values, some of the students’ answers indicated that they had acquired some behavioral patterns from the teachers, such as: egoism, self-love and discrimination, as he used to distinguish between students.